Evaluating the impact of a national strategic leader development programme for UK doctors: myth-busting, mind-changing, mood-enhancing. Issue 3 (3rd November 2021) - McKimm, Judy; Lees, Peter; Armit, Kirsten; Mills, Chloe
Abstract : Background: The drive towards engaging UK doctors in clinical leadership and management has involved many initiatives at various levels. Methods: This paper reports on the findings of an in-depth evaluation of a national medical leadership programme for doctors in the late stages of specialty or general practitioner (GP) training or have just become consultants or GPs. Results: The evaluation clearly demonstrates the impact of this programme and the benefits for the individuals and organisations involved, particularly around stimulating a shift in mood and a major mindset shift in what medical leadership is (and is not) and what they can achieve as medical leaders. The programme structure and activities allowed participants to learn from a range of senior decision-makers about policy and strategic developments and processes. However, the evaluation also highlighted that some pervasive myths still exist around medical leadership and management which, if not addressed, will hamper efforts to fully engage doctors in taking on strategic leadership roles. Conclusion: Clinical leadership programmes are valuable, but must be carefully managed to extract the full value from them.